Indulgence in Death - Robb, J. D. (London Piatkus, 2011)
First it was a limo driver shot through the neck with a crossbow. Then it was a high-priced escort found stabbed through the heart with a bayonet. Random hits, thrill kills, and murderers with a taste for the finer things in life - and death - are making NYPSD Lieutenant Eve Dallas angry.
Keywords: Dallas, Eve (Fictitious character) -- New York (State)--New York -- Policewomen